To What Extent Collateral in PLS Financing Brings Maṣlaḥah? An Analytical Comparison from Islamic Law Outlook with Maqāṣid al-Sharī’ah Index - Lestari, Dini Maulana; Kusuma, Hadri; Sunaryati (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This study aims to compare the level of maṣlaḥah regarding the existence of collateral in Profit and Loss Sharing (PLS) financing from Islamic banking customers and employees standpoints. This is crucial as PLS financing becomes the main characteristic product of Islamic banks, but it emerges as an unfavorable product due to the high financial risk. The existence of collateral plays a pivotal role in this situation to realize maṣlaḥah. This is an explanatory study with a quantitative approach and survey method, considering 400 respondents, particularly 200 Islamic banking customers and 200 Islamic banking employees, who were conveniently obtained at certain time intervals for a one-shot. An Independent sample t-test is used to calculate the comparison level of maṣlaḥah among these two groups. At the same time, Rasch Model analysis is also used to measure the data based on the demographic characteristics of respondents. The result discovers that although there is a slightly different level of maṣlaḥah between Islamic banking customers and employees in PLS finance practice regarding collateral, it still significantly brings benefit, as it aligns with the concept of ta’widh to prevent financial risk. This finding contributes to Islamic banks as a guideline to understand how to operate and enhance the market share of this financing product based on the Rasch Model Analysis.